Studies on the length-weight relationships and condition factors of Mystus cavasius, gulsha tengra from tanguar haor in greater Sylhet region: Biometric Relationships of Mystus cavasius in Tanguar Haor (Journal of the Sylhet Agricultural University, 2026)
The present study focused on investigating the Length-Weight Relationships (LWRs) and condition factors of Mystus cavasius species in Tanguar Haor, Bangladesh, over a time frame from November 2022 to June 2023. A total of 800 Mystus cavasius specimens werecollected using a variety of equipment and nets with the assistance of local fishermen. The length of each fish was measured in centimeters (cm) using a digital slide caliper, while their body weight was determined in g by using a digital balance. The analysis revealed significant differences in the LWR parameters such as rate of change of weight with length (a), weight at unit length (b), condition factor (k), and the co-efficient of correlation (r2), across different months. The maximum value of parameter a (intercept) for M. cavasius was observed in June 2023, reaching 4.4106, whereas the lowest a value occurred in May 2023 of 0.5605. Similarly, the maximum b value of 1.4463 was recorded in May 2023, while the lowest b value of 0.6155 was observed in December 2022. The condition factor (k) exhibited its peak value in March 2023 (0.8400), followed by a subsequent increase to 1.0221 in May 2023. Regarding the coefficient of correlation (r2), the highest value of 0.9531 was documented in December 2022, indicating a strong relationship between length and weight. Conversely, the lowest r2 value of 0.8563 was observed in May 2023, suggesting a relatively weaker correlation during that period. These findings provide valuable insights into the length-weight relationships and condition factors of M. cavasius in Tanguar Haor, such information is crucial for understanding the growth and overall well-being of this species in the study area, thereby facilitating effective fisheries management and conservation efforts.J. Sylhet Agril. Univ. 12(2): 105-116, 2025